MEKANISME PENEGAKAN HUKUM PERKARA PIDANA PORNOGRAFI MELALUI INTERNET - Christianto, Hwian (Veritas et Justitia, 2017)
Internet child pornography is criminalized in three different regulations, i.e. the Criminal Procedural Act (no. 8/1981), Electronic/Digital Information and Transaction Act (Act no. 11/2008) and Pornography Act (Act no. 44/2008).  As a result, law enforcers has to choose between these three different rulings and this may create uncertainty in which ruling from which act should prevail.  The author compares the above acts and reveals the comparative advantage of these three different acts in dealing with child pornography. The main finding here is that each act should be considered supplementary to each other and in combination should be enforced in such a way as to yield justice and legal certainty.